Intra-arterial chemotherapy is more effective than sequential periocular and intravenous chemotherapy as salvage treatment for relapsed retinoblastoma - Schaiquevich, Paula Susana (2013)
BACKGROUND: Treatment of eyes with retinoblastoma failing systemic chemoreduction and external beam radiotherapy is seldom efficacious. This study compares the efficacy and toxicity of intra-arterial ophthalmic artery chemotherapy (IAO) to our historical cohort of sequential periocular and systemic chemotherapy in such patients. PATIENTS AND METHODS: Eighteen eyes (15 consecutive patients) were retrospectively evaluated. Eight eyes received IAO for a median of four cycles (range: 2-9) including melphalan alone (n = 3) or after topotecan and carboplatin (n = 4) or topotecan and carboplatin without melphalan (n = 1). Ten eyes received a median of two cycles (range: 1-3) of periocular topotecan (n = 9) or carboplatin (n = 1) followed by intravenous topotecan and cyclophosphamide in three patients if at least stable disease was achieved. Both groups were comparable for disease extension and prior therapy. RESULTS: No extraocular dissemination or second malignancy occurred and all patients are alive. The probability of enucleation-free eye survival at 12 months was 0.87 (95% CI: 0.42-0.97) for the IAO group, compared to 0.1 (95% CI: 0.06-0.35) for the periocular group (P < 0.01). Ocular toxicity was mild and similar in both groups (mostly mild orbital edema). Systemic toxicity was low for IAO and periocular injection, but children who received sequentially intravenous chemotherapy (n = 12 cycles) had five episodes of grade 4 neutropenia, three of which resulted in hospitalizations. No case in the IAO group presented these complications. CONCLUSIONS: IAO is significantly superior to sequential periocular-intravenous topotecan-containing regimens in eyes with relapsed intraocular retinoblastoma with a more favorable toxicity profile.